Identifying Character Presentation and Motherhood Issue Through the Technique of Focalization in The Witch Of Portobello by Paulo Coelho - Rima Putriani (Universitas Pendidikan Indonesia (UPI), 2015)
The present research investigated the narrative perspective or focalization and motherhood issue inside the novel entitled the Witch of Portobello by Paulo Coelho. The discussion focused on the main character in the story to reveal the character’s traits and her motherhood portrayal through focalization technique. The research utilized qualitative method particularly textual analysis framed by Genette’s (1983) and Culler’s (1997) focalization as the major theory. The result of the present research showed that Athena, the main character in the novel, that were presented to be a strong, independent woman with paranormal abilities who was brave enough to take dangerous risks and difficult paths to satisfy her curiosity. It was also revealed that the focalizations presented Athena to portray the traditional myth of motherhood.Keywords: Character Presentation, Motherhood, Narrative Perspective, Focalization, Literature